Analisis Perubahan Penggunaan Lahan di Kebun Raya Kendari - Bana, Sahindomi (Jurnal Ecosolum, 2020)
Land supply that is fixed while the demand continues to grow makes the land use of a city change toward more profitable activities seen from the surrounding potential. Increasing population and socioeconomic pressure have resulted in the widespread use of natural resources that are not in accordance with their uses, for example encroaching forest areas to build settlements and open land for gardening. Kebun Raya Kendari as anplant conservation areaÂ ex situÂ has a function of conservation, research, education, tourism and environmental services having an area of 96 with conservation plants that are our main and distinctive collection, namely ruruhi (Sisgium sp), singi (Dilenia Serrata Thumb), dan lobe-lobe. Good management of the Kebun Raya Kendari is in need of accurate data and information support. Now, by utilizing the technology capabilities of Geographic Information System and remote sensing, data and information about land cover in the Kebun Raya Kendari can be processed more efficiently. The purpose of this study is to determine changes in land use in the Kebun Raya Kendari. Data analysis of land use change is done by identifying the shape of objects in the satellite imagery that are in the research location. Landsat image interpretation to identify land uses in 1998, 2003, 2008, 2013 and 2018 is done visually. The validation of identification results on field conditions is based on the results of accuracy testing (Ardiansyah, 2014). The land use classification accuracy test is performed statistically by calculating overall accuracy based on a confusion matrix and kappa accuracy. Land use in the Kebun Raya Kendari in 1998, 2003, 2008, 2013 and 2018 was dominated by primary dryland forests and secondary dryland forests. In the period 1998-2018 there was a change in land use dominated by changes in primary dryland forest to open land.